Field reports form for submitting seasonal observations of Iowa birds, Mark Proescholdt, November 25, 1991 - Proescholdt, Market al (1991)
List of birds and locations contributed by Mark Proescholdt with observers Beth Proescholdt, Raymond L. Cummins, Tom Johnson, Russ Widner and others. Included with the field report is a note from Mark Proescholdt to the editors regarding his winter birding. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1991. Epson - sheet feed